2008
DOI: 10.1590/s0100-40422008000200025
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Hg2+ from aqueous solutions by microporous titano- and zircono-silicates

Abstract: Recebido em 7/3/07; aceito em 27/7/07; publicado na web em 26/2/08Being mercury one of the most toxic heavy metals present in the environment, it is of major concern to develop cleanup technologies to remove it from wastewater and recover mercury polluted ecosystems. In this context, we study the potential of some microporous titanosilicates and zirconosilicates for taking up Hg 2+ from aqueous solutions. These materials have unique chemical and physical properties, and here we are able to confirm that they re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…Main relevant properties of ETS-4 related to its sorption capacity have been shown elsewhere [12]. [13]. The centres of black octahedra and grey tetrahedra are occupied by Ti and Si atoms, respectively.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Main relevant properties of ETS-4 related to its sorption capacity have been shown elsewhere [12]. [13]. The centres of black octahedra and grey tetrahedra are occupied by Ti and Si atoms, respectively.…”
Section: Methodsmentioning
confidence: 95%
“…Some studies have demonstrated that titanosilicates are excellent materials to remove Hg 2+ from aqueous solutions [12][13][14][15]. Because of their unique structure, these materials display important chemical and physical properties, such as selective sorption, ion exchange and catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the speciation diagram of Hg (II) species in aqueous solution (Fig. 4) indicates that the dominant Hg(II) species at pH > 4 is Hg(OH) 2 , it has been proved for an initial Hg(II) concentration ≤120 mg dm −3 in solution that Hg(OH) 2 dissolves [10]. Thus, since the Hg(II) concentration used was 50 g dm −3 (<120 mg dm −3 ), the cation exchange process proceed and it was favoured by the lower H + competition.…”
Section: Phmentioning
confidence: 99%
“…It has been shown that the application of microporous titanosilicates for removing priority pollutants such as Hg 2+ and Cd 2+ ions from water may lead to the development of efficient cleanup technologies [1][2][3][4]. Among these microporous materials, the most promising for Hg 2+ ions removal is titanosilicate ETS-4 (Na 9 Ti 5 Si 12 O 38 (OH)·12H 2 O) a prominent member of the class of microporous heteropolyhedra transition-metal silicates.…”
Section: Introductionmentioning
confidence: 99%
“…Microporous zirconosilicates constitute an interesting class of materials owing to their potential applications such as catalysts, sorbents, and ion-exchangers [1,2,3,4]. They are usually referred as heteropolyhedral framework silicates with a "zeolite-like" structure made up of cornershared SiO4 tetrahedra and ZrO6 octahedra.…”
Section: Introductionmentioning
confidence: 99%